Under one common banner: antisemitism and socialist strategy during the 1905–7 Revolution in the Kingdom of Poland. (8th August 2017) - Marzec, Wiktor
ABSTRACT: Marzec investigates socialist strategies in relationship to antisemitism during the 1905–7 Revolution in the Russian-controlled Kingdom of Poland. An extensive, diachronic discourse analysis of political leaflets reveals a dialogical differentiation of political identities and ideological positions. Antisemitism was an important political device used by the National Democracy party (Endecja) to assist in the construction of a new national identity. It represented a certain discursive binary logic that ushered in a need for a negatively perceived and threatening 'outside'. Jews easily became the focus of this mechanism due to the particular sociodemographic conjuncture of events as well as older, more established Judaeophobic tendencies. This antisemitism was, for the same structural reasons, questioned and rejected by the socialist parties that were struggling to maintain class unity. For socialists, the need to prevent the redirection of class anger into ethnic animosities and to secure the united struggle of Polish and Jewish workers were matters of life and death. While general antisemitic attitudes may be perceived as more common in Russian Poland than in Western Europe, nevertheless domestic socialists of all parties and denominations remained firmly against antisemitism and did not accept the 'economic Jew' stereotype that was often a hidden undercurrent of anti-capitalism at the time. A broader overview of the genealogy of divisions among Polish radicals from the 1880s and 1890s and afterwards, up until the tragic rise of antisemitism from 1910 onwards, demonstrates that an anti-antisemitic strategy was adopted, and subsequently kept in place, as the most viable political identity in the given social and political situation. It remained unsuccessful, however, and some socialist writers started to distance themselves from the earlier, virtually unanimous, anti-antisemitic stance.